Bone Health in Premenopausal Women with Coeliac Disease: An Observational Study. - Schraders K; Coad J; Kruger M (MDPI (Basel, Switzerland), 2024)
Low bone mineral density (BMD) is common in adults with coeliac disease (CD), even in individuals adhering to a gluten-free diet (GFD). Women are more likely to have low BMD and have an increased risk of osteoporosis, so women with pre-existing low BMD related to CD are at an even higher risk. BMD assessed by dual X-ray absorptiometry (DXA) and bone quality assessed through quantitative ultrasound (QUS) were investigated in 31 premenopausal women with CD consuming a GFD, and 39 matched healthy controls from the Lower North Island, New Zealand. In addition, bone metabolism and nutrient status were assessed, and four-day diet diaries were used to estimate nutrient intake. No statistically significant differences were found in BMD assessed by DXA between the two groups at the hip, lumbar spine or forearm. However, the parameters measured by the QUS were significantly lower in CD participants. Dietary data indicated significantly lower intakes of energy, dietary fibre, magnesium and phosphorus in women with CD, likely as a result of a reduced intake of wholegrain foods, and suggested that both groups had inadequate intake of calcium. No significant differences were demonstrated in biochemical parameters. BMD and bone biomarkers indicated no differences between coeliac and healthy women in New Zealand. However, these findings suggest that QUS may be more sensitive for the coeliac population, due to the disease's affect on the trabecular bone, and warrant further research.
Keywords: BMC; BMD; CD; DXA; GFD; QUS; bone mineral content; bone mineral density; calcium; coeliac disease; dual X-ray absorptiometry; gluten free diet; protein; quantitative ultrasound; young women; Humans; Celiac Disease; Female; Bone Density; Adult; Premenopause; Diet, Gluten-Free; New Zealand; Absorptiometry, Photon; Middle Aged; Osteoporosis; Case-Control Studies; Nutritional Status; Ultrasonography; Bone and Bones; Young Adult; Biomarkers